Prostate cancer incidence in 43 populations worldwide: An analysis of time trends overall and by age group. Issue 6 (27th November 2015) - Zhou, Cindy Ke; Check, David P.; Lortet‐Tieulent, Joannie; Laversanne, Mathieu; Jemal, Ahmedin; Ferlay, Jacques; Bray, Freddie; Cook, Michael B.; Devesa, Susan S.
Abstract : Prostate cancer is a significant public health burden and a major cause of morbidity and mortality among men worldwide. Analyzing geographic patterns and temporal trends may help identify high‐risk populations, suggest the degree of PSA testing, and provide clues to etiology. We used incidence data available from the International Agency for Research on Cancer (IARC) and certain cancer registries for 43 populations across five continents during a median period of 24 years. Trends in overall prostate cancer rates showed five distinct patterns ranging from generally monotonic increases to peaking of rates followed by declines, which coincide somewhat with changes in the prevalence of PSA testing. Trends in age‐specific rates generally mirrored those in the overall rates, with several notable exceptions. For populations where overall rates increased rapidly and then peaked, exemplified in North America and Oceania, the highest incidence tended to be most pronounced and occurred during earlier calendar years among older men compared with younger ones. For populations with almost continual increases in overall rates, exemplified in Eastern Europe and Asia, peaks were evident among men aged ≥75 years in many instances. Rates for ages 45–54 years did not clearly stabilize or decline in the majority of studied populations. Global geographic variation remained substantial for both overall and age‐specific incidence rates regardless of levels of PSA testing, with the lowest rates consistently in Asia. Explanations for the persistent geographic differences and the continuing increases of especially early‐onset prostate cancer remain unclear. Abstract : Whats' new? Prostate cancer is one of the most commonly occurring malignancies among men worldwide, second only to lung cancer. Nonetheless, geographic and temporal trends in prostate cancer incidence remain understudied. Here, extensive analyses of data from population‐based cancer registries reveal five distinct temporal patterns in global prostate cancer incidence overall. Age‐specific trends were also identified. Notably, rates peaked among men aged ≥75 years in most of the high‐income populations reflecting declining PSA screening at older ages and diagnosis at younger ages. In contrast, rates for men aged 45–54 years did not clearly stabilize or decline in most populations, and PSA testing is not likely to fully explain the rapidly rising rates of early‐onset prostate cancer.